2004
DOI: 10.1128/mcb.24.6.2324-2331.2004
|View full text |Cite|
|
Sign up to set email alerts
|

Lub1 Participates in Ubiquitin Homeostasis and Stress Response via Maintenance of Cellular Ubiquitin Contents in Fission Yeast

Abstract: Ubiquitin-dependent proteolysis plays a pivotal role in stress responses. To investigate the mechanisms of these cellular processes, we have been studying Schizosaccharomyces pombe mutants that have altered sensitivities to various stress conditions. Here, we showed that Lub1, a homologue of Ufd3p/Zzz4p/Doa1p in budding yeast, is involved in the regulation of ubiquitin contents. Disruption of the lub1 ؉ gene resulted in monoubiquitin as well as multiubiquitin depletion without change in mRNA level and in hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…We next examined Ub levels within these transformants by immunoblotting cell extracts with anti-Ub antibodies and examining the level of Ub conjugates. Consistent with previous studies, loss of Doa1 significantly reduced the level of Ub (21,27,31). Using our particular lysis protocol, we found very little unconjugated Ub overall, making the comparison of Ub conjugates more informative for assessing the overall level of Ub.…”
Section: Mvb Sorting Defects Caused By Loss Of Doa1-hse1supporting
confidence: 75%
See 1 more Smart Citation
“…We next examined Ub levels within these transformants by immunoblotting cell extracts with anti-Ub antibodies and examining the level of Ub conjugates. Consistent with previous studies, loss of Doa1 significantly reduced the level of Ub (21,27,31). Using our particular lysis protocol, we found very little unconjugated Ub overall, making the comparison of Ub conjugates more informative for assessing the overall level of Ub.…”
Section: Mvb Sorting Defects Caused By Loss Of Doa1-hse1supporting
confidence: 75%
“…Other analysis has shown that loss of Doa1 dramatically decreases Ub levels (21). Many of the phenotypes of doa1⌬ mutants can be suppressed by overexpressing Ub, suggesting that many of the noted doa1⌬ defects are solely an indirect consequence of lowered Ub levels (21,26,28,31). It is not presently clear how Ub is depleted in the absence of Doa1; however, inhibiting delivery and degradation of ubiquitinated proteins to the proteasome suppresses doa1⌬ growth defects, suggesting that more Ub may be degraded by the proteasome in the absence of Doa1 (24,28,31).…”
mentioning
confidence: 99%
“…Doa1 is a cofactor for the AAA ATPase Cdc48/p97, which helps convey ubiquitinated proteins to the Proteasome (Raasi and Wolf, 2007). Loss of Doa1 causes many cellular defects, including sensitivity to a wide range of drugs and elevated temperature, impaired sorting of ubiquitinated proteins to lysosomes/vacuoles, and defects in DNA repair (Ghislain et al, 1996; Lis and Romesberg, 2006; Ogiso et al, 2004; Ren et al, 2008). Steady-state levels of Ub are decreased in doa1 Δ null mutants, suggesting that Doa1 plays a role in maintaining Ub homeostasis (Ghislain et al, 1996; Mullally et al, 2006; Ren et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Cells were resuspended in ice-cold homogenizing buffer and homogenized using Mini-Beadbeater as described above. FLAG-Prz1 was immunoprecipitated with an agarose-immobilized anti-FLAG antibody as described previously (27). The immunoprecipitates were washed three times with 50 mM HEPES (pH 7.5) containing 150 mM NaCl, 10% glycerol, and 0.1% Triton X-100.…”
Section: Cell Extract Preparation and Immunoblotmentioning
confidence: 99%